Analysis of Factors Associated with the Participation of Couples of Childbearing Age in the Family Planning Program at the Onekore Health Center In 2024 - Ude , Marselina; Marni, Marni; Berek, Noorce Christiani; Nayoan, Christina R. (Jurnal Pangan Gizi dan Kesehatan, 2025)
Background: The Family Planning program plays an important role in reducing the population growth rate and improving maternal and child health. However, the participation of couples of childbearing age in the family planning program in Indonesia, especially in East Nusa Tenggara (NTT) Province, is still relatively low. Puskesmas Onekore is one of the health centers with the lowest coverage of active family planning participants in Ende Regency, which amounted to 21.0% in 2023. Objectives This study aims to analyze the factors associated with the participation of couples of childbearing age in the family planning program. Methods: This study used an analytic survey design with a cross-sectional study approach, which was carried out in the Onekore Health Center working area. The population in this study were all couples of childbearing age, namely women aged 15-49 years. The sample amounted to 92 mothers of childbearing age couples selected by simple random sampling. Results: The results showed that the number of children (p=0.01), attitude towards family planning (p=0.00), and husband's support (p=0.00) were significantly associated with the participation of childbearing age couples in the family planning program. Meanwhile, the availability of contraceptives (p=0.057) and the role of health workers (p=0.069) were not significantly associated.  Conclusions: Husband's support, attitude towards family planning, and number of children are the main factors that influence the participation of childbearing age couples in the family planning program at Onekore Health Center.